Application Of Buddhist Principles in Creating Work-Life Balance in Modern Thai Society - Buaphat, Phrabaidika Sunthorn Piyaputto (Journal of Dhamma for Life, 2026)
This academic article aims to explore the application of Buddhist principles to create work-life balance in modern Thai society, which is facing continuous social, economic, and technological changes. Irregularities between personal and work life are a significant problem affecting people's physical and mental health, especially in the digital age where work and personal life often overlap. This study focuses on analyzing approaches to applying Buddhist principles to enhance quality of life and promote ethics in working effectively together with work. This conceptual article presents a conceptual framework for key Buddhist principles related to life, such as mindfulness, concentration, the Four Noble Truths, and the Threefold Training. These principles can be applied to work in this highly complex era, including the application of Buddhist principles to time management, stress management, and the creation of a virtuous organizational culture. The article also offers practical approaches to applying Buddhist principles in the context of working from home, working in digital environments, and managing workplace relationships. This article focuses on a value analysis of Buddhist principles and considers their application at the individual and organizational levels, both in the context of digital work and increasingly fast-paced and complex lifestyles. This study aims to contribute to the development of a new conceptual framework that can significantly connect Buddhist principles to contemporary life. Both in theory and practice.